A discourse analysis approach to English language translation - Hmood, Saddam Salim (Research Journal in Advanced Humanities, 2026)
This paper examines how discourse analysis enriches translation studies by treating translation as language in use situated within social, cultural, and ideological contexts. Drawing on key discourse traditions—text linguistics, Systemic Functional Linguistics (SFL), and Critical Discourse Analysis (CDA)—and on translation-oriented models (notably Hatim & Mason, Neubert & Shreve, Trosborg, House, and Munday), the study maps analytic tools for pre-translational text analysis, register and metafunctional comparison, shift identification, and quality assessment. Through applied analyses of John F. Kennedy’s famous exhortation and an Arabic–English account of Ramadan practices, the paper demonstrates how register (field, tenor, mode) and Hallidayan metafunctions (ideational, interpersonal, textual) reveal pragmatic and ideological shifts that occur in translation—such as changes in politeness strategies, argumentation patterns, and the reframing of religious specificity into broader cultural terms. The discussion highlights the translator’s agency and the role of intertextuality in producing target texts that are culturally appropriate yet potentially ideologically reframed. The paper concludes that integrating close SFL-based textual analysis with broader CDA perspectives offers a robust, context-sensitive methodology for translation research and pedagogy, and calls for further empirical work across more genres, languages, and multimodal texts to deepen understanding of discourse-driven translation practices.